A rock and a hard place: exploring Fremont territoriality through the pinnacle architecture of Douglas Creek, Rio Blanco County, Colorado - Bauer, Joshua A., author; LaBelle, Jason M., advisor; Van Buren, Mary, committee member; Orsi, Jared, committee member (Colorado State University. Libraries, 2022)
Fremont occupations in northwestern Colorado's Douglas Creek have long captured the attention of travelers and archaeologists. Spanish explorers in the 18th century dubbed its canyon corridor "El Cañon Pintado", due to the impressive rock art peppered throughout. Researchers in the 20th century were captivated by the masonry architecture perched on pinnacle landforms in the area and some wagered that they may have served defensive purposes. This was a warranted premise, considering the known territorial tendencies of Fremont peoples in the Uinta Basin, and the social and environmental changes that occurred around the time of the pinnacle occupations from 1000–1550 CE. This thesis represents the first synthetic study of seven pinnacle structures in Douglas Creek and undertakes to determine whether they were indeed defensive in nature through three research themes. Examined first are the physical conditions associated with the pinnacle sites and finds that they are in naturally defensible settings, such as inconspicuous locations on the landscape and areas with steep slopes, dangerous cliffs, and protective blinds. Architectural components of the structures are then assessed to understand how much planning and effort went into their construction. The results show that the masonry construction attests to attention and care on behalf of the architects, although the structures are not always so meticulously built, perhaps signaling a lack of resources on their part. Finally, viewsheds of each pinnacle site are analyzed, and the results reveal that they provide commanding views of the canyon corridor, arable land, and some storage granaries (another form of masonry architecture attributed to the Fremont). These results suggest that the Douglas Creek Fremont were engaged in a mostly passive form of defensibility but retained the option to actively engage in conflicts. This thesis offers these foregoing insights about the territorial postures assumed by Douglas Creek Fremont during a time of socioeconomic stress stemming from drought, demographic shifts, and increased regional conflicts.
Keywords: climate change adaptations; Formative Era; territoriality; defensive architecture; American Southwest; Fremont